HUBUNGAN PENGEMBANGAN KARYAWAN DENGAN PRESTASI KERJA PADA PT. BANK CENTRAL ASIA TBK. CABANG BENGKULU - Indriasari, Nia (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2015)
Nia Indriasari; This study aims to determined the relationship between the development of employees with performance at PT. Bank Central Asia Tbk. Bengkulu branch. The method used in this study are: qualitative and quantitative analysis using the average distribution analysis, and the Spearman rank correlation test hypotheses. From the calculation of the correlation coefficient, calculated value = 0.91 means the variable relationship with employee performance development at PT. Bank Central Asia Tbk. Bengkulu branch is very strong. Hypothesis tests obtained t value greater than t table is t value = 18.73 whereas t table = 2.003, meaning that if there is a significant relationship between the development of the performance of employees at PT. Bank Central Asia Tbk . Bengkulu branch. Employees at PT. Bank Central Asia Tbk. Bengkulu branch has an interest in any development training held by PT. Bank Central Asia Tbk. Bengkulu branch, employees at PT. Bank Central Asia Tbk. Branch has a high creativity in carrying out the tasks given by PT. Bank Central Asia Tbk. Bengkulu branch so that the creativity that is owned by the employee, the employee is able to improve the quality of work from time to time which can improve the performance of PT. Bank Central Asia Tbk. Bengkulu branch.Key Word: Employee Development, Job Performance